ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS DALAM MENYELESAIKAN MASALAH DIVERGEN BERDASARKAN PERBEDAAN GENDER - Andari Saputra; Zainal Abidin; Cut Intan Salasiyah (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Mathematical representation skills are essential to develop in learning as they play a role in problem-solving and communication. This study aims to explore the mathematical representation abilities of male and female students in solving divergent mathematical problems. Using a qualitative exploratory approach, the research involved four eighth-grade students at MTsN 1 Banda Aceh (two male and two female) as subjects, with data collected through tests and interviews. Data analysis followed the steps of reduction, presentation, and conclusion drawing, while data validity was ensured through triangulation and observer persistence. The findings revealed that male students were able to solve symbolic and model-based problems correctly but had difficulties composing word problems and faced minor challenges in drawing. Female students could construct contextual word problems but struggled with symbolic and model-based problems, and also experienced slight difficulties in drawing.